Os efeitos do estresse financeiro no ambiente de trabalho brasileiro - Souza, Fabio Tosta Gadelha (2017)
The main objective of this paper was to determine whether Brazilian employee’s level of financial stress affects their behavior in the workplace. Specifically, it was tested if individuals with a higher level of financial stress are more likely to: i) miss work, in general; ii) miss work unjustifiably; have excused absences from work; and iv) being subject to punishments at work, as compared to their less stressed colleagues. The study was performed based on a research with 673 employees of 10 different Brazilian companies from different industries, in which participation was voluntary. The level of individual financial stress was determined by the InCharge Financial Distress/Financial Well-Being Scale, created by Prawitz et. al. (2006), in order to use the subjective level of financial stress of the respondents. The tests were applied using the Linear Probability, Probit and Logit models. Our findings were that the financial stress does increase, in a statistically significant manner, the chances of absences from work in general/regardless of motives and of unexcused absences. All three models pointed out in that direction. We have not been able, however, to find significant results in any of the three models that financial stress does increase the chances of excused absences and punishments.